[OA017] Fabrication of an anthropomorphic neonatal 3D printed head phantom, to be utilized as a quality assurance means for the optimization of the neonatal brain T1 and T2 weighted sequences on a 1.5T clinical MRI system. (August 2018) - Kalaitzakis, Georgios; Boursianis, Themistoklis; Kozana, Androniki; Pappas, Evangelos; Raissaki, Maria; Maris, Thomas G.
Abstract : Purpose: To develop an anthropomorphic neonatal 3D printed head phantom which could be used as a quality assurance means for the overall optimization of the neonatal brain clinical T1-weighted (T1w) and T2-weighted (T2w) MRI pulse sequences. Materials and Methods: Tissue-mimicking materials simulating the MR relaxation times of gray and white matter of the neonatal brain were fabricated and enclosed in five glass tube vials. A 3D printed neonatal head anthropomorphic phantom, with radiologically bone-equivalent material was fabricated using anonymized CT scans of a specific neonatal subject. The aforementioned tube vials were encapsidated inside the neonatal head phantom cavity. The anthropomorphic phantom with the encapsidated neonatal brain tissue mimicking glass vials underwent quantitative MR relaxometry utilizing an Inversion Recovery Turbo Spin Echo (IRTSE) sequence to estimate T1 relaxation times and a Car-Purcell-Meiboom-Gill (CPMG) sequence to estimate T2 relaxation times on a clinical 1.5T MRI system. Based on the relaxometric T1 and T2 measurements, the optimal TR and TE values at which the maximum Contrast to Noise Ratio (CNR) between neonatal gray and white matter was recorded were used for the final optimization of the clinical T1w and T2w clinical sequences respectively. Results: T1 and T2 relaxation times of the tissue mimicking materials were in concordance with the relaxation times of a real neonatal brain subject. Clinical MRI system's reproducibility for T1 and T2 measurements remained <5% during a sampling period of 2 months. The anthropomorphic neonatal 3D printed head phantom served as an excellent means for the general optimization of the geometrical, MR signaling and RF safety characteristics, as well as the optimal acquisition times of the clinical neonatal T1w and T2w MRI pulse sequences. Optimal values for the TR and TE MRI parameters were assessed in reference to the maximum CNR between neonatal brain gray and white matter. These were: (TR/TE = 1200 ms/10 ms) for the T1wSE and (TR/TE = 9500 ms/280 ms) for the (T2wTSE) sequences respectively. Conclusion: Overall clinical T1w and T2w sequence optimization for neonatal brain imaging at a 1.5T clinical MRI system was accomplished with the aid of an anthropomorphic neonatal 3D printed head phantom encapsidated with neonatal brain tissue mimicking materials.